UNIPLACES : a housing platform for student accommodation : creating a global brand - Gonçalves, André Alberto Cavaleiro (2017)
Uniplaces, a Lisbon based startup, has become the fastest growing international website for booking student accommodation and it currently operates in forty cities across nine European countries. Uniplaces was able to change a difficult, bureaucratic and old-fashioned process of booking accommodation, into an easier, enjoyable and modern one, by moving it online. To serve the increasingly mobile student population, Uniplaces is creating a trusted, global brand for student accommodation. It wants to become the reference for students when they are looking for accommodation. To achieve this goal Uniplaces decided to redesign its international expansion strategy in Europe by building different regional sales areas. This case study offers an overview of the European student housing sector focusing on a future scenario of how Uniplaces can manage the consolidation and expansion of its operations across Europe, as current business development resources are becoming too thinly spread across the continent. These new regional areas group markets that have similar dynamics regarding the student housing sector. Regional area 1 is formed by Portugal, Spain, Italy and France; Regional area 2 by the United Kingdom; and Regional area 3 by Germany, the Netherlands, Austria and Poland. United Kingdom is a separate case where the sector has already matured, thus the dynamics observed in this market cannot be addressed in the same way as other European markets.